Soroprevalência e fatores associados à infecção por Covid-19 em profissionais da educação após a primeira onda na cidade de Fortaleza, Ceará 2020 - França, Pâmela de Castro (2024)
The covid-19 pandemic has triggered a series of control measures around the world, including the closure of schools in order to reduce the transmission of the virus. This study investigated the seroprevalence of IgG anti-SARS-CoV-2 antibodies in teachers and employees of private schools in Fortaleza, Northeast from Brazil, after the first wave. This is a cross-sectional analytical survey study, with data collected in the form of a serological survey between October and November 2020. 2.341 professionals participated in the study and after screening, 1.901 questionnaires were used, with a predominance of women (68.4%), with 47.1% of participants were between 31 and 45 years old. The majority of participants lived in houses (63.1%) with up to three residents (56.9%). A considerable portion of those interviewed reported the absence of people diagnosed with covid-19 at home (57.6%) and 68.4% commented that they knew someone who had died from covid-19. IgG antibodies were detected in 152 of the 1,901 samples, with a positive seroprevalence of 8.0% (95% CI: 6.8-9.3). Among seropositive participants, 48.3% did not report previous illnesses same to covid-19. Identification of factors associated with infection can guide more effective and targeted control strategies. This was the first large-scale prevalence study carried out on education workers in Brazil immediately after the first wave of the covid-19 pandemic.